Automated pH Monitoring and Controlling for Hydroponics Cultivation - Rahim, Mohamad Raihan; Mat Akir, Rohaida (Evolution in Electrical and Electronic Engineering, 2021)
Hydroponics is a plant cultivation method that does not involve any use of soil. It just requires a solvent that contains nutrients. pH concentrations are critical to ensure that plants consume the optimum nutrient needs and late action in controlling the pH level may impact on plant quality and growth rate. As recommended, pH levels required by the most hydroponic plant are between 5.5 to 6.5. Using Arduino Uno as the primary microcontroller, the project develops a prototype of an automated IoT hydroponics system. A pH sensor is used throughout the entire project development to monitor the pH level. The NodeMcu is used to interconnect system devices to the Blynk Apps, a platform used for this project to implement the Internet of Things (IoT). The experiment was carried out to evaluate the accuracy of the pH sensor as well as another important component, the water pump. From the results, the system has lower error range which is below ± 5% and has better tolerance when compared to pH tester. Within 14 days observation, the system able to maintain the pH level at the recommended range. Based on the experiment sequences for each component and a full functionality experiment of the pH automated system, the system met the project’s goal.